Designing a Learning Space for Unified Collaboration and Communication between Universities, Industry and the Public Sector (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
The goal of this paper is to present theoretical and technical approaches, which acts as guidelines for the design of multifunctional rooms (MFR) enabling communication and collaboration. Furthermore, to define a method to mix key trends in education technology, pedagogy and room design together to facilitate various types of scenarios and users. The Norwegian Ministry of Foreign Affairs is financing a program in Higher Education, Research and Development in the Western Balkans 2010-2016 (HERD). A sub program within HERD focus on the energy sector. This paper refers to a project within the energy sector called: Quality Improvements of Master Programs in Sustainable Energy and Environment (QIMSEE). The projects members in QIMSEE are eight universities (Trondheim, Belgrade, East Sarajevo, Tuzla, Sarajevo, Banja Luka, Podgorica, and Skopje). The main goal of the project is to improve the quality of education at Master's programs. A milestone in this project process is to enhance interconnections between universities, industry and the public. The need for a common technological platform and standards for cooperation and communication is fundamental. A multifunctional room (MFR) or “learning space” will be set up at each location to support activities defined in the project synopsis.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.